Communicating Awareness About COVID-19 Through Songs: An Example From Ghana - Thompson, Rachel G. A.; Nutor, Jerry John; Johnson, Julene K. (Frontiers in Public Health, 2021)
Research has shown that music can be used to educate or disseminate information about public health crises. Grounded in the edutainment approach, we explored how songs are being used to create awareness about the COVID-19 in Ghana, a sub-Saharan African country. Common music-sharing websites were searched, and 28 songs met study inclusion criteria. We conducted a thematic analysis of the song lyrics. Most lyrics were in English, Ghanaian Pidgin English, Akan, Ga, or Dagbani. Reflecting the multilingual population of Ghana, half of the songs contained three languages to convey their message, and only five songs were in one language. Eight themes emerged from the analyses: COVID-19 is real and is infectious, emotional responses, public health guidelines, expelling the virus, prayer as method to stop the virus, unity and hope. We show that songs have the potential as a method for rapidly sharing information about emerging public health crises. Even though, it is beyond the scope of this study to draw conclusions about the reception and impact of songs on awareness and knowledge, the study shows that examining song lyrics can still be useful in understanding local attitudes toward COVID-19, as well as strategies for promoting preventive behaviors. We note that additional multidimensional efforts are needed to increase awareness among the general public about the COVID-19 pandemic.